Tinjauan Ilustrasi Cover Novel Harry Potter Edisi Indonesia Karya Nicolas Fiber Ditinjau Dari Elemen Visual - Dongan Maruli Tua Sinaga; R. Triyanto (Mahesa Research Center, 2020)
The cover illustration of the Harry Potter novel has many variants in various parts of the world, by bringing their respective nusions represented by each element presented by the illustrator. The cover illustration of the Indonesian edition of the Harry Potter novel by Nicholas Filbert is one of the official covers of the Indonesian edition of the Harry Potter novel. By reviewing the visual elements presented by the illustrator qualitatively, it can be seen that the visual elements are related to the concepts and nuances offered by the illustrator. This study aims to review the visual elements in the cover illustration of Harry Potter and the Goblet of Fire. By collecting data in the form of images, articles, as well as sources related to the cover, illustrators, which are the sources of researchers in reviewing and finding new findings related to visual elements in the cover illustration of Harry Potter and the Goblet of Fire. By using a qualitative method, from the data obtained by the researcher, the researcher gets information that will be the result related to the visual cover element. The findings of this study indicate that of all the visual elements reviewed, it is found that the illustrator tries to make the illustrations The difference is quite noticeable from cover illustrations from other parts of the world. The illustrator also tries to present the uniqueness of the illustrator, namely the illustration that is dense and fills all the empty spaces and is directed at one of the Indonesian peculiarities which is expressed in visual elements making Batik a visual reference, namely on color and composition.